ANALYZE THE INFLUENCE OF FEATURE USE PAYLATER ON THE SHOPEE APPLICATION (Case Study of Communities in the District Menganti-Gresik) - Anisa Dwi Indriyani; Bachtiar Rahman Halik (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2024)
This study aims to analyze the effect of convenience, interest rates and perceived risk on theinterest of the people in Menganti district to use the Paylater feature on the Shopee Application. The unit ofanalysis in this study is the people who live in the Menganti district who have used Shopee Paylater as many as83 people. Samples were taken using sampling quotas. the technique of determining samples from a populationthat have characteristics to the desired amount (quota). Researchers select samples based on certain criteria sothat researchers get the appropriate sample. Data analysis was performed using statistics using SPSS version26. Based on the results of data analysis using the t test, it is knows that interest rates partially have asignificant influence on interest in using Shopee Paylater. Meanwhile, convenience and perceived risk do notsignificantly influence in using Shopee Paylater. So for the company are advised to Pay attention to interestrates so that this feature remains popular with the publik